Willingnes to Pay dan Ability to Pay Pelayanan Sanitasi di Kota Yogyakarta - Naris Dyah Prasetyawati; Evi Gravitiani; Sunarto Sunarto (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
The sanitary conditions in densely populated settlements such as in Yogyakarta are quite heterogeneous, in terms of both quality and quantity. The parameters in the healthy home assessment include components of the house, sanitation and behaviour. The economic valuation method is one of the ways used to provide a quantitative value of the goods and services produced by natural resources and the environment. The purpose of the study is to determine the valuation of the Contingent Valuation Method (CVM) value. CVM method is one of direct economy assessment methods through Willingness to Pay (WTP) question. This study aims to determine the economic conditions in the settlements in the city of Yogyakarta. This type of research is an observational retrospective design. Samples were 597 families living in the city of Yogyakarta taken by using multi-stage random sampling. Economic valuation data covered income, willingness and ability to pay taps, waste management and effluent treatment from households, were obtained using a questionnaire. The results of this study on the economic valuation of votes obtained WTP of taps water (PDAM) was in the range of 2,500 – 4,000 IDR / 10m3 / month with ATP for 7,585 IDR / 10m3 / month, WTP for garbage levy was in the range of 2,000 - 4,000 IDR/ month with ATP for 13,594 IDR / month, while WTP for wastewater management was in the range of 3,000 IDR/ month with ATP 2,870 IDR/ month. A total of 48.41% survey respondents have an income of less than 1,500,000 IDR per month so that the economic condition of Yogyakarta is in a low category.